HUBUNGAN MOTIVASI BELAJAR PADA MATA PELAJARAN MENJAHIT UNTUK MENINGKATKAN KOMPETENSI PESERTA DIDIK PROGRAM KESETARAAN PAKET C DI SKB GRESIK - Febrianty, Veronica; Artha, I Ketut Atmaja Johny (J+PLUS UNESA, 2024)
Motivation to learn is the existence of encouragement from outside and within students that creates a spirit of learning that can provide direction for learning activities to achieve the desired goals. Competence is a mastery of skills, abilities, knowledge, values, and attitudes that can be possessed by each individual sourced from education, training, and experience, as well as learning. The purpose of this study was to determine the relationship between learning motivation in sewing subjects to improve the competence of students in the package C equivalency programme at SKB Gresik. This research uses a quantitative approach, with product moment correlation analysis techniques with sampling using the slovin formula, the number of samples in this study was 48 students of the package C equivalency programme. The research location is at SKB Gresik. Data collection techniques are observation, questionnaires, and documentation. The results of the Pearson product moment correlation test between the learning motivation variable and the variable to improve competence, the Pearson correlation value is 0.760, which means that the relationship between learning motivation and improving competence is in the high category, based on the interpretation of the correlation coefficient. This means that the higher the learning motivation, the more the competence of students in learning increases..